Possible Involvement of Hepatitis B Virus Infection of Hepatocytes in the Attenuation of Apoptosis in Hepatic Stellate Cells - Sasaki, Reina (PLoS One, 2016)
BACKGROUND: The induction of apoptosis in hepatic stellate cells (HSCs) is a promising therapeutic strategy against hepatitis B virus (HBV)-related hepatic fibrosis. The underlying mechanisms of apoptosis in HSCs, however, are unknown under consideration of HBV infection. In this study, the effects of HBV on apoptosis and endoplasmic reticulum (ER) stress signaling in HSCs were examined. METHODS: The effects of conditioned media (CM) from HepG2.2.15 on apoptosis induced by the proteasome inhibitor MG132 in LX-2 and HHSteC were studied in regard to c-Jun. In combination with c-Fos, c-Jun forms the AP-1 early response transcription factor, leading to AP-1 activation, signal transduction, endoplasmic reticulum (ER) stress and apoptosis. RESULTS: In LX-2 cells, MG132 treatment was associated with the phosphorylation of c-Jun, activation of AP-1 and apoptosis. However, in the presence of CM from HepG2.2.15, these phenomena were attenuated. In HHSteC cells, similar results were observed. HBV genomic DNA is not involved in the process of HSC apoptosis. It is possible that HBeAg has an inhibitory effect on MG132-induced apoptosis in LX-2. We also observed the upregulation of several ER stress-associated genes, such as cAMP responsive element binding protein 3-like 3, inhibin-beta A and solute carrier family 17-member 2, in the presence of CM from HepG2.2.15, or CM from PXB cells infected with HBV. CONCLUSIONS: HBV inhibits the activation of c-Jun/AP-1 in HSCs, contributing to the attenuation of apoptosis and resulting in hepatic fibrosis. HBV also up-regulated several ER stress genes associated with cell growth and fibrosis. These mechanistic insights might shed new light on a treatment strategy for HBV-associated hepatic fibrosis.